2019
DOI: 10.1101/645788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Second Harmonic Generation Spectroscopy of Membrane Probe Dynamics in Gram-Positive Bacteria

Abstract: Bacterial membranes are complex mixtures with dispersity that is dynamic over scales of both space and time. In order to capture adsorption onto and transport within these mixtures, we conduct simultaneous second harmonic generation (SHG) and two photon fluorescence measurements on two different gram-positive bacterial species as the cells uptake membranespecific probe molecules. Our results show that SHG can not only monitor the movement of small molecules across membrane leaflets, but is also sensitive to hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The measured time-resolved SHS kinetic traces depicted in Fig. 2 can be fit, using our established model, to determine the molecular transport rates for the various bacterial interfaces (i.e., OM, PM, S-layer, and CM) (20)(21)(22)(23)(24)(25)(26)(27)(28). It is found that MG cation transport across the OM proteins in the OM and the pores in the S-layer is similarly rapid and was deduced as 0.04 and 0.02 s À1 , respectively.…”
Section: Molecular Transport Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured time-resolved SHS kinetic traces depicted in Fig. 2 can be fit, using our established model, to determine the molecular transport rates for the various bacterial interfaces (i.e., OM, PM, S-layer, and CM) (20)(21)(22)(23)(24)(25)(26)(27)(28). It is found that MG cation transport across the OM proteins in the OM and the pores in the S-layer is similarly rapid and was deduced as 0.04 and 0.02 s À1 , respectively.…”
Section: Molecular Transport Ratesmentioning
confidence: 99%
“…This characteristic mechanism has previously been employed to monitor molecular adsorption and transport across phospholipid membranes in biomimetic model liposomes (12)(13)(14)(15)(16)(17)(18)(19) and living cells (20)(21)(22)(23)(24)(25)(26)(27)(28). When SHG-active molecules adsorb onto the exterior surface of the membrane, they align with one another because of the similarity of the interaction driving the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Although we observe Ebp puncta at the septal membrane, it is possible that Ebp are polymerized at the septum, possibly within punctate microdomains, and subsequently move within the cell membrane towards the cell hemisphere for anchoring by SrtA. Microdomains in the bacterial cell membrane are dynamic and fluidic in nature (Los and Murata, 2004; Miller et al, 2019). Furthermore, new surface-exposed Ebp were only seen at the cell hemipsheres with or without cell wall inhibition.…”
Section: Discussionmentioning
confidence: 77%
“…This characteristic mechanism has previously been employed to monitor molecular adsorption and transport across phospholipid membranes in biomimetic model liposomes (12)(13)(14)(15)(16)(17)(18)(19) and living cells. (20)(21)(22)(23)(24)(25)(26)(27)(28) When SHG-active molecules adsorb onto the exterior surface of the membrane, they align with one another due to the similarity of the interaction driving the adsorption process. This oriented ensemble of SHG-active molecules gives rise to a coherent SHS response, the intensity of which scales as the square of the molecular surface density.…”
Section: Introductionmentioning
confidence: 99%